Intense upconverted ultraviolet emission of Er3+ through confined energy transfer in Yb3+/Er3+ co-doped Rb3InCl6 - Wen Zhang; Wei Zheng; Ping Huang; Dengfeng Yang; Zhiqing Shao; Wei Zhang; Hao Zhang; Zhi Xie; Jin Xu; Xueyuan Chen (Nature Communications)
Abstract Yb3+/Er3+ activated upconversion (UC) materials have been widely applied in many advanced technologies owing to their high UC efficiency in the visible region. However, it is challenging to achieve efficient ultraviolet (UV) UC luminescence (UCL) in Yb3+/Er3+ system, due to the dense energy levels of Er3+ that impose deleterious nonradiative relaxation. Herein, we report a strategy to liberate the UV-UCL of Er3+ based on the confined energy transfer in Yb3+/Er3+ co-doped 0D Rb3InCl6 with a low phonon energy and a large interionic distance. This facilitates the population of Er3+ at the 4G11/2 state, which yields intense upconverted UV emission at 384 nm, with a much higher UV-to-green ratio (I 384/I 554 = 0.864) than that of traditional UC materials ( < 0.1). By leveraging the intense upconverted UV emission of Er3+, we demonstrate the application of Rb3InCl6:Yb3+/Er3+ nanocrystals as a NIR-to-UV transducer for NIR-triggered anion exchange of CsPbX3 perovskite nanocrystals with high efficiency and good controllability. These findings offer an approach for the exploration of novel UC materials via energy transfer and crystal lattice engineering towards versatile applications.